Utilization of cellulose and ulvan from the green seaweed Ulva lactuca in the development of composite edible films with natural antioxidant properties - Gomaa, Mohamed; Al-Badaani, Arwa A.; Hifney, Awatief F.; Adam, Mahmoud S. (Journal of applied phycology, 2022)
Cellulose and ulvan were extracted sequentially from the green seaweed Ulva lactuca and were used for the development of edible films with natural antioxidant properties. The composite films were composed of cellulose, polyvinyl alcohol, glycerol as plasticizer and different ulvan concentrations. The interaction between ulvan and film components was described by FT-IR analysis, which confirmed the formation of hydrogen bonding interactions between cellulose and ulvan. The incorporation of ulvan into the cellulose films markedly increased film thickness, water solubility and water vapor permeability, whereas the oxygen permeability was decreased. Additionally, the composite films showed good barrier properties against UV and visible light. The moisture sorption of the films was modelized using Peleg's model which exhibited a satisfactory fitting to the experimental data. The thermal stability was markedly enhanced in the presence of high concentration of ulvan. Furthermore, the incorporation of ulvan to cellulose films enhanced its antioxidant properties as measured by total antioxidant assay (TAC), ferric reducing antioxidant power (FRAP), hydroxyl radical scavenging activity (HRSA) and iron chelating activity (ICA). The use of water and 3% acetic acid as food simulants indicated that the FRAP was higher in case of water, while the opposite trend was observed for the HRSA and ICA. Overall, the developed cellulose/ulvan films could have potential uses in food packaging to promote the shelf-life of different food products.